Assessment of the neutralizing potency of ovine antivenom in a swiss mice model of Bothrops jararaca envenoming - Ferreira, J.; Bastos, M. F. [UNESP]; Pelizon, A. C. [UNESP]; Peres, C. M. [UNESP]; Cavalcante, D. P. [UNESP]; Sartori, A. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos, 2005)
Alternative sources of anti-ophidic serum are being investigated due to the secondary effects associated with types I and II hypersensitivity reactions. In the present study we raised and evaluated the protective effect of an ovine antibothropic serum in a Swiss mice envenoming model. Ovine antiserum was obtained by immunization with seven increasing doses of bothropic venom associated with adjuvants. The neutralizing ability was tested by the lethal activity (2 LD50) neutralization and serum and splenic venom levels after antivenom administration to experimentally envenomed mice. The antiserum effect on local edema was also tested by injection of venom/antivenom mixtures into the mice footpads. Ovine antiserum neutralized lethal activity and also significantly decreased serum and splenic venom levels. However, this antiserum was not able to mediate any protective effect on edema triggered by bothropic venom.
Keywords: Bothrops jararaca venom; ovine antiserum; venom levels; edema; ELISA